Changes in Long-term Mortality in Patients with Myocardial Infarction History According to the LIS Luberetskiy registry - S. Y. Martsevich; N. P. Zolotareva; A. V. Zagrebelnyy; M. L. Ginzburg; O. M. Drapkina (Столичная издательская компания, 2022)
Aim. The aim of the research was to study the dynamics of distant cases of the disease that underwent AMI in 2005-2007 (LIS registry) and in 2014 and 2018 (LIS-3 registry), discharged from the same hospital of the Lyubertsy District Hospital (LDH).Material and methods. The study was conducted on the basis of two registries - a retrospective-prospective register LIS (Lyubertsy investigation of death), which was conducted in the Lyubertsy district of the Moscow region, all cases of check-ups in the AMI hospital for a 3-year period (2005- 2007) and the prospective register LIS-3 (11/01/2013 - to the present), which included patients admitted to the cardiology department of the Lyubertsy District Hospital No. 2 with the correct diagnosis of Acute coronary syndrome with and without ST segment elevation. With patients discharged from the hospital, a telephone contact was established no earlier than 1 year after discharge to clarify the life status, and in case of death - to find out its causes. Search for patients who did not answer the phone call, was using by the study of the archive of the polyclinic, with database statistics. Longterm cases of the LIS were compared with LIS-3 registers, clinical demographic characteristics and risk indicators in patients in the LIS and LIS-3 registers were also compared, differences in drug therapy before the onset of AMI and after discharge from the hospital register between LIS and LIS3 were analyzed.Results. Out of 327 patients, the registry included 104 (31.8%) patients discharged in 2014 and 223 (68.2%) in 2018. When comparing the longterm mortality curves of the LIS and LOS-3 registers, a significant difference was noted. The LIS-3 study revealed more frequent referrals for antiplatelet agents (20% vs 16%), statins (11.6% vs 2.0%). Less commonly, diuretics began to be prescribed at the prehospital level. After discharge from the hospital in the LIS-3 registry, a decrease compared to the LIS registry, more frequent prescription of antiplatelet agents (97.5% vs 85.0%), anticoagulants (1.1% vs 0%), statins (96.5% vs 67.0%), beta-blockers (93.3% vs 81.0%). Less commonly, diuretics are prescribed at discharge from the hospital.Conclusion. The present study of the LIS-3 registry showed a significant decrease in the incidence of those who had AMI, which occurred 15-20 years after the LIS registry was conducted.